Seven Principles of Anatomical Pedagogy in Proverbs: A Hermeneutic Study of Numerical Proverbs Based on Proverbs 6:16-19 - Aska Aprilano Pattinaja; Victor Pattianakotta (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2024)
The pedagogical element is powerful in the Book of Proverbs as the primary teaching material for wisdom seekers. Interestingly, in Proverbs 6:16-19, a unique pedagogical element emerges because it is organized based on the anatomy of the human body, eyes, tongue, hands, heart, and feet. It closes with a complete picture of the human being, a false witness. Some previous studies have only focused on discussing it in terms of the structure of Proverbs 6 in the opening (prologue) of Proverbs 1-9 without examining its pedagogical elements. For this reason, this study aims to explore the pedagogical principles in Proverbs 6:16-19 as an essential lesson for a life pleasing to God and very unique because of the peculiarities of human anatomy. Based on the Hermeneutic Analysis of Wisdom Literature Sub Genre, this study found several things, namely: First, Synthetic parallelism in verse 16 emphasizes the understanding of God's hatred and disgust for sin; Second, Seven pedagogical principles of Proverbs numerical anatomy, namely: humility, honesty, mercy, purity, deliberation, honesty, and unity. The results of this study serve as a warning for believers to practice the principles of pedagogy as moral and ethical values.